The Importance of Mirna Expressions in Infertilty - Gökalp, S.; Akgül, Bünyamin; Akgül, Bünyamin; Özçakır, T.; Vatansever, H. S. (Wiley, 2016)
Implantation process is controlled with endometrium, factors secreted by the embryos and in accordance with these factors embryo and/or endometrium via receptors on. More than 700 human MicroRNA (miRNAs) that are small noncoding RNAs were shown to play an important role in intracelluler cycle regulation in both normal and pathological conditions. In this study we aim to identify miRNAs and controlling molecules expressions in different time period of endometrium in fertile and infertile cases.
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY